Aspetos da vida universitária e a síndrome de burnout - Jordani, Paula Cristina; Zucoloto, Miriane Lucindo; Bonafé, Fernanda Salloume Sampaio; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Leibniz Institute for Psychology (ZPID), 2012)
Aim: To estimate the prevalence of Burnout Syndrome in dental students, from a public university, and compare the mean scores obtained in each dimension of the Oldenburg Burnout Inventory (OLBI-S), according to the sociodemographic variables of interest. A total of 235 students participated in the study. Methods: The psychometric characteristics of OLBI-S were estimated. The comparison of Exhaustion and Disengagement mean scores was performed, using the Student’s t test and Analysis of Variance (ANOVA). Results: A total of 72.8% of the participants were women and the mean age was 21.0 ± 1.8 years. After the removal of three items, OLBI showed adequate factorial validity and reliability. Of the surveyed students, 61.7% had Burnout Syndrome, 22.1% Exhaustion and 4.7% Disengagement. A higher Disengagement mean score was observed for students who did not chose the Dentistry course as their first choice, and who consider teachers to be incompetent/reasonable. Those whose initial expectations were frustrated, with poor course performance, who already used medication due to their study load, and who thought about quitting the course, had higher mean scores of both Exhaustion and Disengagement. Conclusion: There is a high prevalence of Burnout Syndrome, with a significant relation to sociodemographic variables.

Objetivo: Estimar a prevalência da Síndrome de Burnout em estudantes de Odontologia de uma universidade pública e comparar os scores médios obtidos em cada dimensão do Inventário de Burnout de Oldenburg (OLBI-S) segundo as variáveis sociodemográficas de interesse. Participaram 235 estudantes. Métodos: As características psicométricas do OLBI-S foram estimadas. A comparação dos scores médios de Exaustão e Distanciamento foi realizada pelo teste t de Student e Análise de Variância (ANOVA). Resultados: Dos participantes 72,8% eram mulheres e a média de idade foi de 21,0±1,8 anos. Após a remoção de três itens, o OLBI-S apresentou adequada validade fatorial e confiabilidade. Dos estudantes, 61,7% apresentaram a Síndrome de Burnout, 22,1% Exaustão e 4,7% Distanciamento. Observou-se maior score médio de Distanciamento nos estudantes que não escolheram o curso de Odontologia como primeira opção e que consideraram os professores incompetentes/razoáveis. Aqueles cujas expectativas iniciais foram frustradas, com desempenho ruim no curso, que já consumiram medicação devido aos estudos e que já pensaram em desistir do curso apresentaram maiores scores médios tanto de Exaustão quanto de Distanciamento. Conclusão: A prevalência da Síndrome de Burnout é alta com relação significativa com variáveis sociodemográficas.
Aspects of university life and burnout syndrome
Keywords: Professional fatigue; Odontology; Public health; Esgotamento profissional; Oodontologia; Saúde pública